2018
DOI: 10.4081/ripppo.2018.310
|View full text |Cite
|
Sign up to set email alerts
|

The perception of the illness and the self-efficacy in the management of emotions in cardiac patients

Abstract: Cardiac rehabilitation is the sum of psychological, physical and social treatments that are offered to cardiac patients to maintain or regain an active position in society. This study wants to evaluate changes in the perception of the illness and in the self-efficacy of the management of positive and negative emotions in patients who went through cardiac rehabilitation. Sixty-seven patients (20 females, 47 males) were selected within the cardiac rehabilitation unit in the Hospital of Cittadella (Italy). Illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…As described above, our results showed that both brief interventions enhanced the management self-efficacy for chronic and cardiac disease, particularly mindfulness practice. This result is concordant with those reported by Marogna et al [24], who found that, after a cardiac rehabilitation intervention, the management of emotions had a positive impact on self-management of the disease. It is important to note that the two interventions tested in this study focused on emotional factors and, therefore, the results regarding the improvement of self-efficacy for managing chronic disease are a sign of the effectiveness of both interventions in providing patients with greater confidence in their ability to handle the emotional distress caused by the disease; moreover, neither of the interventions was directly focused on the development of behavioral and cognitive abilities for managing cardiac disease, adherence to therapy, or recognition of symptoms, which supports the connection between emotional wellbeing and self-efficacy development.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As described above, our results showed that both brief interventions enhanced the management self-efficacy for chronic and cardiac disease, particularly mindfulness practice. This result is concordant with those reported by Marogna et al [24], who found that, after a cardiac rehabilitation intervention, the management of emotions had a positive impact on self-management of the disease. It is important to note that the two interventions tested in this study focused on emotional factors and, therefore, the results regarding the improvement of self-efficacy for managing chronic disease are a sign of the effectiveness of both interventions in providing patients with greater confidence in their ability to handle the emotional distress caused by the disease; moreover, neither of the interventions was directly focused on the development of behavioral and cognitive abilities for managing cardiac disease, adherence to therapy, or recognition of symptoms, which supports the connection between emotional wellbeing and self-efficacy development.…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence that selfefficacy for the management of chronic diseases [22] and, specifically, CVDs [23] influences affective balance and health perception. Moreover, a cardiac rehabilitation intervention on the management of emotions has shown a positive impact on the management of the disease in cardiac patients [24].…”
Section: Subjective Emotional Wellbeing and Management Self-efficacy ...mentioning
confidence: 99%
“…Moreover, The Relationship Between Cardiac Self-efficacy and 6-Minute Walking Test (N = 220, 100%) patients with low cardiac self-efficacy have a higher incidence of cardiovascular events. 34 Marogna et al 35 showed that factors related to a patient's disease perception are more likely linked with self-efficacy than other factors, such as disease knowledge. This finding might be used in clinical settings to consider patient perceptions of their HF to improve adherence to healthy behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This study illustrates that IP partly differs between men and women. Gender differences in IP have also been shown for patients with other chronic diseases, such as inflammatory bowel disease [ 30 ] and heart disease [ 17 , 31 ]. Rassart et al showed that women with congenital heart disease (CHD) experienced more symptoms (identity dimension) and indicated a worse emotional response to the CHD than men [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rassart et al showed that women with congenital heart disease (CHD) experienced more symptoms (identity dimension) and indicated a worse emotional response to the CHD than men [ 17 ]. In a study by Marogna et al 2018 women in cardiac rehabilitation also reported a greater impact of their heart disease on the emotional response dimension in IPQ, compared to men [ 31 ]. We show that the self-reported severity of gout was associated with the perceptions of gout (Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%